Design of a Vaccine Registration System to Improve Health Services at the Food, Maritime, and Agriculture Sub-Department of South Jakarta - Salfa Nandalusia; Yayan Hendrian; Ahmad Hafidzul Kahfi (Journal of Innovative and Creativity, 2025)
The development of this web-based vaccine registration system aims to address the challenges of manual and telephone-based registration methods, while enhancing the efficiency and quality of vaccination services at the Food, Maritime, and Agriculture Sub-Department (KPKP) of South Jakarta. By leveraging information technology, this system offers an online registration platform that allows the public to access vaccination services without the need for physical presence. The application features a user-friendly interface, structured data management, and effective vaccination scheduling. The implementation of this system is expected to improve service punctuality, reduce queues, and facilitate data monitoring and management by KPKP staff. The results of the User Acceptance Test (UAT) indicate that all core functionalities operate as intended and are well-received by users, demonstrating the application's capability to deliver a faster, more accurate, and responsive solution for the vaccination registration process, thereby supporting accelerated vaccination efforts in the South Jakarta region.